Managing of foreign exchange risk in software development company - Zeľo, Tomáš (2011)
This master thesis discusses the field of foreign exchange risk management and assesses efficiency of this type of risk management within FFastFill plc. The thesis contains two major parts. The first part, which contains the first and the second chapter, focuses on theoretical characteristics of foreign exchange market and sequentially defines the terms of foreign exchange exposure and foreign exchange risk. This part of thesis discusses hedging strategies and matters that are related to the selection of optimal hedging strategy. The second part of thesis contains the third and the fourth chapter. This part analyses the company from various perspectives and consequently analyses and quantifies the magnitude of company's translation and transaction exposure. The aim of this analysis is to assess company's current hedging strategy and to propose the optimal hedging strategy.